Application of the allometric scale for the submaximal oxygen uptake in runners and rowers - Tartaruga, M. P.; de Medeiros, M. H.; Alberton, C. L.; Cadore, E. L.; Peyre-Tartaruga, L. A.; Baptista, R. R.; Coertjens, M.; Kruel, L. F. M. (Biology of Sport, 2010)
Background: The aim of the current study was to determine the allometric exponents for runners and rower`s metabolic cost, while also verifying the relation of performance with and without the allometric application. Methods: Eleven runners (age: 22.3±10.4 years; height: 174±8.8 cm; body mass: 61.7±9.3 kg; maximum oxygen uptake ( •VO2max): 56.3±3.9 ml.kg-1.min-1) and fifteen rowers (age: 24±5.4 years; height: 185.5±6.5 cm; body mass: 83.5±7.2 kg; •VO2max: 61.2±3.4 ml.kg-1.min-1) carried out a specific progressive maximum test. The allometric exponent was determined from the logarithmic equation Log y = Log + b Log x, where x is the mass, y is the VO2max (l.min-1), a is one constant and b is the allometric exponent. The data were analyzed using descriptive and comparative statistics (independent T test of the Student), with p<0.05 (SPSS version 13.0). Results: The allometric exponent of the rowers was 0.70 and that of the runners was 1.00. Significant differences were found between the fat mass percentage, with higher value for rowers, suggesting that this variable may influence the behavior of the allometric exponent and consequently of the basal metabolic rate. Conclusions: Scaling may help in understanding variation in aerobic power and in defining the physiological limitations of work capacity.